Growth media characterization based on pine bark and sawdust - Sánchez-Córdova, Tito; Aldrete, Arnulfo; Cetina-Alcalá, Víctor M.; López-Upton, Javier (Instituto de Ecología, A.C., 2016)
Forest nursery production in containers in México mainly uses peat moss, vermiculite and agrolite (standard mixture). Sawdust and pine bark are subproducts of the forest industry which can be used as substrates. The objective of this work was the characterization of five mixtures using pine bark, sawdust, peat moss, vermiculite. Evaluation included physical (bulk density, total porosity, air porosity and easily available water) and chemical (pH, electrical conductivity and cation exchange capacity) characterization. Bulk density varied from 0,31 to 0,51 g m- 3 while the standard mixture was 0,15 g m- 3. Total porosity varied from 77 to 91% compared to the standard mixture with 84%. Air porosity varied from 8 to 20% compared to the standard mixture with 8%. Easily available water varied from 4,8 to 9,9% compared to the standard mixture with 17,7%. pH of the mixtures with bark and sawdust varied from 4,52 to 7,70 while the standard mixture was 3,87. Electrical conductivity varied from 1,84 to 2,69 ds m- 1 while the standard mixture was 1,13 ds m- 1. Cation exchange capacity varied from 43,6 to 89,4 meq/100 g while the standard mixture was 60,4 meq/100 g. Physical properties of mixture 4 (20% of bark + 80% of sawdust) are similar to standard mixture, but not the chemical properties. This mixture is a promising substrate for forest nursery production.